Growth and Meat Quality of Grass Carp (Ctenopharyngodon idellus) Responded to Dietary Protein (Soybean Meal) Level Through the Muscle Metabolism and Gene Expression of Myosin Heavy Chains - Wang, Xiaoyu; Liu, Guoqing; Xie, Shouqi; Pan, Lei; Tan, Qingsong (Frontiers in Nutrition, 2022)
The aim of this study was to investigate the effect of dietary protein level (soybean meal) on growth performance, flesh quality of grass carp and the related molecular mechanism. The results showed that appropriate dietary protein level improved the growth performance, hardness and pH of muscle, while decreased muscle crude lipid content and cooking loss, and altered the antioxidant capacity and metabolic enzymes activities. In addition, appropriate dietary protein promoted the gene expression of myhc-1, myhc-4, myf5, myod, myog, and fgf6a, whereas inhibited that of myhc-7, myhc-2, mrf4, and mstn. Transcriptome profiling of muscle revealed the flesh quality-specific differences were related to tight junctions and intramuscular fat accumulation. GSEA showed that fatty acid metabolism and oxidative phosphorylation were down-regulated in SM5 compared with SM1. To conclude, appropriate protein level improved the growth and flesh quality by regulating muscle antioxidant capacity and gene expression of myhcs and fat metabolism-related signaling molecules.